2010
DOI: 10.1016/j.pedhc.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors and Home Allergen Exposure in Children With Asthma

Abstract: Introduction-The objective of this study was to determine the association between sociodemographic factors and the elimination of allergen sources from homes of asthmatic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…At the individual level, lower parental education level has been linked to higher levels of asthma triggers such as environmental tobacco smoke. 27 However, data linking neighborhood education level with asthma is sparse. The protective influence of increased education level in a child's neighborhood may represent an important construct for increased access to collective resources and capital, 28 medical care, or healthy behaviors, reduced stress, or decreased allergens.…”
Section: Discussionmentioning
confidence: 99%
“…At the individual level, lower parental education level has been linked to higher levels of asthma triggers such as environmental tobacco smoke. 27 However, data linking neighborhood education level with asthma is sparse. The protective influence of increased education level in a child's neighborhood may represent an important construct for increased access to collective resources and capital, 28 medical care, or healthy behaviors, reduced stress, or decreased allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Although nearly 50% of youths with asthma experience an acute exacerbation annually (Akininbami, 2009), low-income, minority youths are disproportionately at higher risk for uncontrolled asthma and asthma-related Emergency Department (ED) visits (Zhang, Lamichhane, & Diggs, 2016). The causes of poorly controlled asthma are multifactorial and include environmental exposures to triggers in the home and community (e.g., second hand smoke, rodents, mold, dust mites), poor condition knowledge and self-management skills, access to care barriers including difficulties with medication administration in the school, and hardships associated with poverty (Authors, 2014 Authors, 2017a; Borowsky et al, 2013; Bruzzesse et al, 2012; Camacho-Rivera et al, 2014; Lang et al, 2013; Ungar, Cope, Kozyrskyj, & Paterson, 2010). Caregiver psychosocial factors such as life stress and depressive symptoms further heighten risk for child asthma morbidity (Authors, 2015; Clawson et al, 2016; Feldman et al, 2011, 2013; Lim, Wood, Miller, & Simmens, 2011; Martin et al, 2013; Tibosch, Verhaak, & Merkus, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In another longitudinal study, Klinnert, Kaugars, Strand, and Silverira (2008) found in 98 children who enrolled in their study at 9-24 months of age that family psychological factors including caregiver single parent status and family factors consistent with a negative emotional environment were related to active asthma at age four. Unger, Cope, Kozyrskyj, and Paterson (2010) found that children with asthma who had mothers with no postsecondary education were more likely to have ETS exposure, as compared to those who had postsecondary education or higher. Also the children's mothers' employment status was significantly (p = .0002) related to home environment quality.…”
Section: The Social Environment and Asthmamentioning
confidence: 93%